Perlindungan Hukum Terhadap Anak Korban Narkotika dalam Proses Peradilan - Nicha Suwalla; Khairul Riza; Irpan Husein Lubis (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2022)
Purpose: The purpose of writing this journal is to find out the diversion arrangements at the level of investigation of children who commit narcotic crimes, and find out the rights violated in investigations and efforts to protect the law against children who commit narcotic crimes. Methodology: The method used is a normative approach, namely through the study of legislation and literature, and the empirical approach is through field research by conducting a series of interviews with respondents and informants to obtain field data. Results: The results of the study show that the regulation of diversion at the level of investigation of children who commit narcotics crimes means that there is absolute authority from investigators to carry out diversion efforts against children who commit narcotic crimes, but of all the cases handled so far none of the diversion attempts have been successful. applied. The rights that are violated in the investigation of children who commit narcotics crimes are that the investigator does not prioritize the principle of the best interests of the child, the investigator does not provide legal assistance and other assistance, the investigator does not ask for expert opinion in carrying out the investigation, and does not notify the right to obtain legal assistance. Efforts to protect the law against children who commit criminal acts of narcotics abuse in investigations, namely asking parents and Community Advisors to accompany children during the investigation process, provide guidance to children while undergoing a period of detention at the investigative level, and complete the investigation process within a time limit of 7 (seven) days with an extension of 8 (eight) days.